Strategi dan Metode Pembelajaran Pendidikan Agama Islam Di Madrasah Ibtidaiyah - Eliza Khoirunnisa; Wibawati Bermi (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
Islamic religious education plays a very important role in human life, because religion is a guide to realizing a peaceful, meaningful and dignified life. Realizing the importance of the role of religion for human life, religious values in the life of each individual become a necessity that must be pursued through education both family, school and community education. Islamic Religious Education aims to shape students to become human beings who believe and have devotion to God Almighty and have noble morals in their personal, social, national and state life. Optimally Islamic religious education must be able to educate students in order to have maturity or maturity in thinking, believing and devotion to Allah Besides that, they are also able to practice the values they get in the educational process. Therefore, religious values must be instilled in children from an early age. Apart from parents, teachers also have a very important role in instilling religious values as a foundation from an early age or starting Madrasah Ibtidaiyah (MI)